Predicting Hospital Length of Stay among Pediatric Patients in University of Maiduguri Teaching Hospital - Modu Isa, Alhaji; Zannah , Umar; Garba Ngulde, Shuaibu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Hospital Length of Stay (LOS) is a critical metric in healthcare management, reflecting the duration a patient spends in a hospital facility. Among pediatric patients experiencing trauma, LOS serves as a key indicator of the complex interplay between injury severity, treatment efficacy, and the overall healthcare trajectory. Understanding and predicting the factors influencing LOS in this specific population are crucial for optimizing patient care, resource allocation, and healthcare system planning. This study investigates Hospital Length of Stay (LOS) among Pediatric Trauma Patients with the primary goal of understanding and predicting the factors influencing the duration of hospitalization for this demographic. The cross-sectional study is based on pediatric trauma patients admitted to the Emergency Department of the University of Maiduguri Teaching Hospital, Borno State, Nigeria, in 2023. Data encompass demographic characteristics, injury details, and LOS for patients under 17 years, derived from hospital records. The RTS scoring system, incorporating Glasgow Coma Scale, Systolic Blood Pressure, and Respiratory Rate, is used to predict pediatric trauma patients' LOS. Multiple regression analysis is employed to identify factors influencing LOS. Results of the study outlines the scoring criteria for RTS parameters and presents regression analyses highlighting significant predictors of LOS, such as Injury Type and Breath/Minute. The model's robustness is confirmed by the Coefficient of Determination (R Square = 0.960), signifying its effectiveness in explaining and predicting LOS variability.